Desenvolvimento e classes sociais no Brasil – uma análise da segunda experiência desenvolvimentista a partir da tensão colonialidade/decolonialidade - Lira, Bruno Ferreira Freire Andrade (2020)
The debate on development has distanced itself from sociological reflections and has been monopolized by economic knowledge. Economicism, based on orthodox imperialism spurned by the advancement of neoliberal rhetoric and the financialization of everyday life since the 1980s, empties the idea of development by reducing it to a model of economic growth that marginalizes other dimensions of social life. In the face of this restlessness, we propose to resignify the conception of development from decolonial thought and French economic sociology. While the former identifies a strong tension between coloniality/decoloniality that refers to disputes within the capitalist/modern/colonial world-system between forms of domination/resistance; the second is to reflect how development should be understood in all the multiple dimensions – whether economic, political, social, historical – understanding their dynamics in a procedural and relational way. Once this resignification of development is established, we propose to analyze the relationship between possible transformations in the structures of the social class and the second Brazilian developmental experience, during the years 2006/14, based on coloniality/decoloniality tension. For this, the first part of this research is to deconstruct the hegemonic idea of development situated in the economic perspective of calculability, predictability and rationality. From the critique of French economic sociology – through Bourdieu, Steiner, Boltanski and Lebaron – we propose to critically scrutinize the financial domination and the foundations of this: market, glocal subject and economic knowledge. Next, we seek to reflect the development within Latin America and the Caribbean throughout Latin American and Caribbean social thought from the developmentalism of the cepalinos, which are criticized by dependentists, to decolonial thinking and the construction of coloniality/decoloniality tension. In the latter I see the presence of a matrix of colonial power exercised by the capitalist/modern/colonial world-system that promotes forms of coloniality of power, knowledge and being. The forms of (r)existence take place through the decolonial gyrus, a movement of rupture with coloniality, generating decoloniality based on demarketization, social emancipation and dialogical plurality. Once the theoretical frameworks are recognized, we seek to build a methodology based on social markers of coloniality/decoloniality tension of ambivalent, mediating and interpretative character. By mentioning these under development I choose the three foundations of financial domination – market, glocal subject and economic knowledge – and we propose to identify their ambivalence in the tension between coloniality/decoloniality. Through these methodological tools, we reflect the universe of this research that is the second Brazilian developmental experience and its economically oriented social policies – minimum wage, credit grant and family grant program – located during the second Lula administration (2007-2010) and the first of Dilma (2011-2014). Later, with the use of markers, we verified if there were in fact possible transformations of the structure of social classes in Brazil from its relationship with the recent developmental model. In the end, based on the tension coloniality/decoloniality, we debated about the limits of the changes undertaken by the recent Brazilian developmentalism. Here, by not confronting other elements that colonize our daily lives – such as race and gender – and the pair of privilege/oppression, it was not possible to promote colonial ruptures to modify the intersection of multiple forms of domination and social classification demonstrated by the dialogue between decolonial thinking and intersectionality.